Correlation Between Serum TSH Levels Within Normal Range and Serum Lipid Profile - Luxia, Liu; Jingfang, Liu; Songbo, Fu; Xulei, Tang; Lihua, Ma; Weiming, Sun; Ying, Niu; Gaojing, Jing; Qianglong, Niu; Yujuan, Li; Dan, Wu; Fang, Yang; Huiping, Guo; Pei, Song (Hormone and Metabolic Research, 2020)
The aim of the work was to investigate the correlation between serum TSH (thyrotropin) levels within normal range and serum lipids. A total of 1962 subjects with normal thyroid function were enrolled. The subjects were divided into four groups according to the quartiles of serum normal TSH levels, [Q1 (0.27–1.68) mIU/l, Q2 (1.69–2.35) mIU/l, Q3 (2.36–3.07) mIU/l, and Q4 (3.08–4.20) mIU/l]. The effect of serum normal TSH levels on serum lipid profiles of different age or gender was analyzed. The total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) levels of the Q3 group and TG levels of the Q4 group were higher than those of the Q1 group in youth (p <0.05). The TC levels of the Q3 group were higher than those of the Q2 group in middle age (p <0.05). The LDL-C levels of middle age or elderly were higher than those of youth at the same TSH levels (p <0.05), while the TC levels of middle age were higher than those of youth in Q1, Q3, or Q4 group (p <0.05), and the TC and HDL-C levels of elderly were higher than those of youth in the Q2 group (p <0.05). The TG levels of the Q3 group were higher than those of Q1 group in males (p <0.05). The LDL-C levels of the Q3 group were higher than those of the Q1 group in females (p <0.05). In conclusion, the normal serum TSH levels were found to be closely related to serum lipid profiles, and with increasing TSH levels, serum lipids levels increased gradually.
Keywords: thyroid; thyroid-stimulating hormone; serum lipids